ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN KEPUASAN PELANGGAN - Rifki Karta Surya; Muhammad Iqbal Fasa (PT. Intelek Cendikiawan Nusantara, 2024)
Marketing strategy is a strategy used by companies on an ongoing basis to win market competition in the long term. The purpose of writing this journal is for companies to have a product strategy in terms of increasing customer satisfaction. A product is anything that a producer can offer to be noticed, requested, searched for, purchased, and used or consumed by the market to fulfill the needs or desires of the relevant market. Products can provide tangible and intangible benefits that have the potential to satisfy customers. Customer satisfaction is the most important factor for business development. Product strategy will have an impact on customer satisfaction. Therefore, satisfied customers will repurchase a product and recommend the product to other customers.